La propriété matérielle des archives photographiques de presse. Enjeux juridiques - Samuel Bonnaud-Le Roux (In Situ)
There are many archive services which today hold significant collections of press photos. These may come from a variety of different origins—often unidentified ones—and this makes it difficult to identify the material property of the elements which make up the collections. Photojournalism has always involved a broad variety of actors, and practices where the material medium of the photograph is concerned are by no means standardised. Digitisation is now changing the relations between the traditional actors in the processes of picture creation and is also increasing the number of pictures available to the general public. The conflicts which have arisen between photographers and agencies often concern the restitution to the photographers of their originals or the photographers’ access to these originals when copies of them were not kept. In this context, the jurisprudence relating to practices in the transfer between photographers and press agencies of ownership of photographic works may throw some useful light on the archival questions which arise at the end of the process. It is also necessary to examine how the photo collections entered public archives depots, since these modalities of accession may influence questions of ownership. In this article, the different ways a photo collection may enter a public archive depot are examined. Depending on whether the collection was purchased or donated, the consequences are not the same where the ownership of the originals is concerned. The possibility for archival services to apply the principle of prescriptive acquisition to the private photo collections they hold is examined, in cases where the origins of the collections are not clearly determined and where there is no document to stipulate the intentions of the person or service that produced the collection.